Case Report: Neonatal Urinary Ascites Without Hydronephrosis: A Rare Case of Anterior Urethral Valve and Diverticulum in Preterm Newborn - He, Yue; Lin, Sam Bill; Li, WenXuan; Sun, YuBo; Tang, LiangFeng; Zhang, Rong (Frontiers in Pediatrics, 2022)
The deformation of congenital obstruction of the anterior urethra is rare in male infants. The anterior urethral valve (AUV) and diverticulum are not common causes of distal urethral obstruction, which may be significant but difficult to diagnose in time. We describe a premature infant who was diagnosed with AUV as part of a diverticulum in the anterior urethra and was presented as massive urinary ascites without hydroureters and hydronephrosis. After indwelling abdominal tube and urinary catheterization, the infant’s massive ascites were resolved, while urethral obstruction had successful treatment by Holmium laser. We suggest that the presence of urinary ascites in fetuses and neonates should be considered as a warning against urinary malformations.